2020
DOI: 10.1016/j.ijmultiphaseflow.2020.103258
|View full text |Cite
|
Sign up to set email alerts
|

The local slip length and flow fields over nanostructured superhydrophobic surfaces

Abstract: The local slip behavior and flow fields near the gas-liquid interface (GLI) of a Newtonian liquid flowing past a superhydrophobic surface with periodic rectangular grooves are investigated using molecular dynamics (MD) simulations. The saturated vapor of the liquid fills the groove to form the GLI. A flat GLI is introduced by carefully adjusting the channel height to make the liquid bulk pressure equal to the coexistence pressure. The setup with the flat GLI allows for an accurate determination of the local sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In another series of studies, the channel height has been carefully adjusted to maintain a flat liquid/air interface in molecular dynamics simulations (Bao, Priezjev & Hu 2020;Ren et al 2021). Using certain microtrench SH surfaces, the Cassie state has been stabilized for turbulent flows (Xu et al 2020(Xu et al , 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another series of studies, the channel height has been carefully adjusted to maintain a flat liquid/air interface in molecular dynamics simulations (Bao, Priezjev & Hu 2020;Ren et al 2021). Using certain microtrench SH surfaces, the Cassie state has been stabilized for turbulent flows (Xu et al 2020(Xu et al , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…2019). In another series of studies, the channel height has been carefully adjusted to maintain a flat liquid/air interface in molecular dynamics simulations (Bao, Priezjev & Hu 2020; Ren et al. 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, an excessively large groove width is not conducive to drag reduction. Bao et al [85] found that the relationship between local and effective slip length is not consistent with the continuity hypothesis for both lateral and longitudinal layouts The slip length, l S , and temperature jump coefficient, k S , commonly used to address the slip at the surface. Reproduced with permission.…”
Section: Layout and Shape Of The Microstructuresmentioning
confidence: 99%